Interpersonal leadership and organizational climate in the Nursing Department of a public hospital - Morales-Malpartida, Rosa L. (2019)
The objective of this research was to determine the relationship between interpersonal leadership and the organizational climate perceived by the nursing professionals at the Carlos Showing Ferrari II-E Maternal and Child Hospital, during 2018. The ethical considerations were applied. It was a study with a quantitative, relational approach , descriptive, prospective and cross-sectional, with a sample population of 43 non-probabilistically selected nurses, who answered the interpersonal leadership and organizational climate questionnaires, previously validated and reliable. The descriptive analysis was performed and the hypothesis was verified by the non-parametric Spearman Rho test for a p ≤ 0.05. The results show that 55.8% (24) of the sample perceived moderate level interpersonal leadership, 34.9% (15) high and 9.3% (4) low. 51.2% (22) perceived an organizational climate to improve, 34.9% (15) healthy and 14% (6) unhealthy. The existence of a positive and significant relationship between teamwork and between the managerial skills of interpersonal leadership and the organizational climate was verified [rs = 0.817 and rs = 0.654, with p <0.05 respectively] It is concluded that interpersonal leadership and Organizational climate perceived by the nursing professionals of the II-E Maternal and Child Hospital Carlos Showing Ferrari, Huánuco - 2018, are significantly related.